The Role of Transforming Growth Factor Beta and Smad Receptors in Determining Prognosis in High-Grade Primary Brain Tumors: Glioblastoma Multiforme - Gürsoy, Güven; Barutçuoğlu, Mustafa; Sivrikoz, Oya Nermin; Gökalp, Sevtap; Vatansever, Seda (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction High-grade primary brain tumors cause serious morbidity and mortality. This study aimed to investigate the role of transforming growth factor beta (TGF-β) and suppressor of mothers against decapentaplegic (Smad) receptors in high-grade primary brain tumors.Material and Method Thirteen patients with a pathological diagnosis of glioblastoma multiforme were included in the study. Pathological preparations of each patient were analyzed retrospectively in histochemistry and immunohistochemistry laboratories. Transforming growth factor beta 1, TGF-β2, TGF-β3, Smad 1/2/3, Smad 6, and Smad 7 stainings were evaluated, and the immunoreactivity densities were examined.Result We found out an increase in the expression of TGF-β1 and TGF-β3 protein. Regarding the inhibitin receptors, Smad 6 showed much more expression than Smad 7. Thus, we found that Smad 6 has a protective effect and role in the tissue. Immunhistochemically, TGF-β family stains, which are activated by types I-and -II receptors, and the stainless staining of the Smad family might also be showing that the TGF-β family is taking action with a secondary pathway other than the Smad family.Conclusion In addition to Smad family receptors, Shc-GBR2, SARA, and Ras-Erk1/2 receptors should be investigated in future research. After that, the prognosis, diagnosis, and patient-based chemotherapy strategies for the treatment of glioblastoma multiforme may take a more prominent role.
Keywords: glioblastoma multiforme; transforming growth factor beta; smad proteins; endothelial-mesenchymal transition